Hierarchical protein targeting and secretion is controlled by an affinity switch in the type III secretion system of enteropathogenic Escherichia coli. (6th November 2017) - Portaliou, Athina G; Tsolis, Konstantinos C; Loos, Maria S; Balabanidou, Vassileia; Rayo, Josep; Tsirigotaki, Alexandra; Crepin, Valerie F; Frankel, Gad; Kalodimos, Charalampos G; Karamanou, Spyridoula; Economou, Anastassios
Abstract: Type III secretion (T3S), a protein export pathway common to Gram‐negative pathogens, comprises a trans‐envelope syringe, the injectisome, with a cytoplasm‐facing translocase channel. Exported substrates are chaperone‐delivered to the translocase, EscV in enteropathogenic Escherichia coli, and cross it in strict hierarchical manner, for example, first "translocators", then "effectors". We dissected T3S substrate targeting and hierarchical switching by reconstituting them in vitro using inverted inner membrane vesicles. EscV recruits and conformationally activates the tightly membrane‐associated pseudo‐effector SepL and its chaperone SepD. This renders SepL a high‐affinity receptor for translocator/chaperone pairs, recognizing specific chaperone signals. In a second, SepD‐coupled step, translocators docked on SepL become secreted. During translocator secretion, SepL/SepD suppress effector/chaperone binding to EscV and prevent premature effector secretion. Disengagement of the SepL/SepD switch directs EscV to dedicated effector export. These findings advance molecular understanding of T3S and reveal a novel mechanism for hierarchical trafficking regulation in protein secretion channels. Synopsis: Sequential delivery of translocators before effectors by the type III secretion system of Gram‐negative bacteria depends on altering binding affinities of chaperone/secretory protein complexes to the export apparatus. In vitro reconstitution assays show that hierarchical recruitment of such complexes depends on interactions between the peripheral gatekeeper protein SepL and the translocase EscV. SepL is membrane‐associated and interacts with EscV. SepL interacts with middle substrate‐loaded chaperones. A complex of SepL and its chaperone SepD increases the affinity of middle substrate/chaperone complexes for EscV and decreases that of late substrate/chaperone complexes. Late substrate/chaperone complexes interact with EscV with high affinity when SepL/SepD are detached. Abstract : In vitro reconstitution shows that the Escherichia coli gatekeeper SepL and chaperone SepD prevent premature effector protein secretion by regulating their affinity to the export machinery.